Rheumatoid Arthritis and Acute Coronary Syndrome: Changing Clinical Presentation - HS Natraj Setty; Rahul S Patil; Sumit Bhatnagar; Animesh Guptha; TR Raghu; Jayashree Kharge; BK Geetha; CN Manjunath (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2017)
Rheumatoid arthritis is a chronic systemic inflammatory disease, Rheumatoid arthritis can affect the pericardium, myocardium, and endocardium. RA increases cardiovascular morbidity and mortality by accelerated atherosclerosis. Patients with RA are at a twofold increased risk for myocardial infarction and stroke. Rheumatoid arthritis is often complicated by thrombocytosis. Thrombocytosis usually occurs during the active clinical stages of RA. We report a 40 year old male who presented with sudden onset of back pain, neck pain and gum bleeding he was diagnosed to have Acute Anterior Wall Myocardial Infarction (AWMI) and successfully under went PCI to LAD with uneventful follow up.